Tsurumi Shunsuke et les frontières du pragmatisme, 1945-1960 - Michael Lucken (Ebisu: Études Japonaises)
Tsurumi Shunsuke (1922-2015) is best known in France for his work in historical sociology and his role in the 1960s anti-Vietnam War movement. Less well known, however, is his philosophical work in the early part of his career, between the end of the Second World War and the renewal of the Japan-US Security Treaty. This article explores this seminal period, during which he contributed to the introduction of American pragmatism to Japan, before adopting a much more critical stance towards it. Such a shift is highly instructive, both in terms of Tsurumi’s own intellectual journey and, more generally, the possibilities and limits of a decentralized appropriation of pragmatism.